Pengaruh Harga, Lokasi, Dan Variasi Produk Terhadap Loyalitas Pelanggan Nice So Cabang Tlogomas Kota Malang - Fizzaki Faris Alim; Achmad Agus Priyono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The recovery of Indonesia’s retail sector after the pandemic has shown a positive trend, driven by increased household consumption and economic activity. Due to the increased competition, businesses must increase customer loyalty as a critical component of their long-term viability.. This study aims to analyze the effect of price, location, and product variety on customer loyalty at Nice So Tlogomas Branch. A quantitative approach was employed, with data collected through questionnaires distributed to 95 respondents who had made at least two purchases. The data were analyzed using multiple linear regression with SPSS. The results indicate that partially, price, location, and product variety each have a positive and significant effect on customer loyalty, with product variety emerging as the most dominant variable. Simultaneously, all three variables significantly influence customer loyalty, as evidenced by an F-test significance value of 0.000 (less than 0.05). Furthermore, the coefficient of determination (Adjusted R²) of 0.609 shows that 60.9% of customer loyalty variation  is explained by these variables, while the remaining 39.1% is influenced by other factors not included  in the model. These findings suggest that competitive pricing, strategic and accessible locations, and diverse, relevant product offerings play a crucial role in enhancing customer satisfaction and fostering long-term customer loyalty in the retail sector.. Keywords: Customer Loyalty, Price, Location, Product Variety, Modern Retail